Poor CD4/CD8 ratio recovery in HBcAb-positive HIV patients with worse immune status is associated with significantly higher CD8 cell numbers - Malagnino, Vincenzo; Cerva, Carlotta; Teti, Elisabetta; Campogiani, Laura; Compagno, Mirko; Foroghi Biland, Luca; Saderi, Laura; Armenia, Daniele; Salpini, Romina; Svicher, Valentina; Sotgiu, Giovanni; Iannetta, Marco; et al. (Scientific reports, 2021)
Low CD4+ cell count in patients with human immunodeficiency virus (HIV) and hepatitis B virus (HBV) coinfection during combination antiretroviral therapy (cART) has been described; however, notably few studies have investigated coinfected patients positive for antibodies to the HBV c antigen (HBcAb). An observational retrospective study enrolling 190 patients was conducted by grouping patients with respect to HBV status and recording CD4+ T cell counts and percentages (CD4%), CD8+ T cell counts and percentages (CD8%), and the CD4+ to CD8+ T cell ratio (CD4/CD8) at the time of HIV diagnosis, at the start of treatment and at months 1, 2, 3, 4, 5, 6, 12, and 24 after beginning cART. One hundred and twenty patients (63.2%) were negative for previous HBV infection, while 70 (36.8%) were HBcAb-positive. A significant increase in the CD4/CD8 ratio was recorded in HIV monoinfected subjects compared to HBV coinfected patients from months 4 to 12 from the beginning of cART ( p value = 0.02 at month 4, p value = 0.005 at month 5, p value = 0.006 at month 6, and p value = 0.008 at month 12). A significant increase in the absolute count of CD8+ T lymphocytes was described from months 2 to 24 from the start of cART in the subgroup of HBV coinfected patients with an AIDS event at the onset of HIV infection. The presence of HBcAb was observed to be associated with reduced CD4/CD8 ratio growth and a significantly higher proportion of subjects with CD4/CD8 < 0.45 in the HIV/HBV coinfected group. A significant increase in the CD8 T cell count was shown up to 24 months after the initiation of effective cART in the subgroup of patients with the worst immune status.